ARITHMETIC FUNCTIONS VERIFYING A RECURRENCE RELATION, COMPOSITIONS AND BELL POLYNOMIALS - Alegri, Mateus (2024)
In the work we apply the Z-transform to the recurrence of Cauchy convolution type, satisfied by several arithmetic functions, to obtain its solution in terms of the complete Bell polynomials. One of the most important arithmetic function used here is sigma1(n), the function that sum all positive divisors of n. Our main result can be applied to find a closed formula for the number of k-colored partitions, sum of triangular numbers and more.